A Critical Discourse Analysis of English Electronic News Reports of Environmental Suistainability - Nguyễn Thị Hạ Quyên (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
With the boom of the mass media, the reality of environmental problems, potential solutions and benefits of environmental sustainability is well known to the public. With regard to discourse features, news reports bear certain typical properties differentiating them from other types of discourse. This thesis investigates the discourse features of English electronic news reports (EENRs) on environmental sustainability in terms of lexical, grammatical and textual features in light of critical discourse analysis (CDA) by Fairclough (2001). A combination of mixed research methods was applied for this research with qualitative method including descriptive analysis on the support of quantitative approach. 69 EENRs on the topic concerned were collected from the UN News website. The study results reveal that words and expressions related to the topic of environmental sustainability, formal words, content words and metaphors can be characterized as typical lexical features of the discourse. The transitivity, passive and active voice, modes of sentences, relational modality, pronouns, expressive modality and cohesion are also recorded as grammatical features of the discourse. The headlines and the leads are crucial elements constituting textual structure of the news reports studied. The findings of this thesis have served as a base for the researcher to put forward some implications for the teaching and learning English in terms of vocabulary, grammar and textual structure. In addition, this thesis can also be a reference for teachers, learners or those who are interested in writing news reports and can provide them with a better understanding in a new approach of discourse analysis.